Posterior Cervical Inclinatory Foraminotomy for Spondylotic Radiculopathy Preliminary - Chang, Jae-Chil (The Korean Neurosurgical Society, 2011)
Posterior cervical foraminotomy is an attractive therapeutic option in selected cases of cervical radiculopathy that maintains cervical range of motion and minimize adjacent-segment degeneration. The focus of this procedure is to preserve as much of the facet as possible with decompression. Posterior cervical inclinatory foraminotomy (PCIF) is a new technique developed to offer excellent results by inclinatory decompression with minimal facet resection. The highlight of our PCIF technique is the use of inclinatory drilling out for preserving more of facet joint. The operative indications are radiculopathy from cervical foraminal stenosis (single or multilevel) with persistent or recurrent root symptoms. The PCIFs were performed between April 2007 and December 2009 on 26 male and 8 female patients with a total of 55 spinal levels. Complete and partial improvement in radiculopathic pain were seen in 26 patients (76%), and 8 patients (24%), respectively, with preserving more of facet joint. We believe that PCIF allows for preserving more of the facet joint and capsule when decompressing cervical foraminal stenosis due to spondylosis. We suggest that our PCIF technique can be an effective alternative surgical approach in the management of cervical spondylotic radiculopathy.